2013
DOI: 10.1002/pbc.24512
|View full text |Cite
|
Sign up to set email alerts
|

A case study of personalized therapy for osteosarcoma

Abstract: The approach described through this illustrative case study is broadly applicable and might be used for other solid tumors in canines as well as in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…In the study of osteosarcoma progression and metastasis, key advances have been made by the Comparative Oncology Program at the National Institutes of Health (NIH) through the study of dogs, including the recognition of the role of ezrin [12,[72][73][74][75]. Furthermore, early clinical trials are now ongoing in dogs in conjunction with the Children's Oncology Group in North America, an approach that will quickly ascertain the effectiveness of osteosarcoma therapy, owing primarily to the much larger number of dogs with osteosarcoma compared with humans [12,72,[76][77][78]. With time and additional canine trials, researchers believe the success of this approach will become readily apparent.…”
Section: (I) Osteosarcomamentioning
confidence: 99%
“…In the study of osteosarcoma progression and metastasis, key advances have been made by the Comparative Oncology Program at the National Institutes of Health (NIH) through the study of dogs, including the recognition of the role of ezrin [12,[72][73][74][75]. Furthermore, early clinical trials are now ongoing in dogs in conjunction with the Children's Oncology Group in North America, an approach that will quickly ascertain the effectiveness of osteosarcoma therapy, owing primarily to the much larger number of dogs with osteosarcoma compared with humans [12,72,[76][77][78]. With time and additional canine trials, researchers believe the success of this approach will become readily apparent.…”
Section: (I) Osteosarcomamentioning
confidence: 99%
“…Dasatinib was chosen since it was one of the most effective at inducing cell death in the primary tumor cells, and it is well tolerated in humans and is readily available. The dog was still in remission 24 months following the primary diagnosis [ 136 ]. It remains to be determined whether such method may be more broadly feasible in human patients.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, this array could be very useful in the future for screening RTK activity in osteosarcoma tumor samples. Another method for personalizing targeted therapy has recently been reported in a canine osteosarcoma case [ 136 ]. Primary tumor cells were isolated prior to chemotherapy treatment and cell survival was screened using a panel of SMIs.…”
Section: Discussionmentioning
confidence: 99%
“…This opens the possibility to use the explant technique to assess postoperative treatment options (eg, drug screening) as described in a dog patient. 17 To this end, we have shown that drug testing using patient-derived cells is feasible in 2D cultures and in 3D spheroid culture. 38 There are several ways to improve further the success or to modify the here described method.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] As we assumed it to be difficult to optimize enzymatic digestion protocols for each single tissue type affected by sarcoma and because pleural effusion is mainly performed in patients with end-stage lung metastases only, we explored here the potential to obtain patient-derived cell lines from sarcoma patients using the explant technique. Notably, apart from incidental case reports, [20][21][22][23][24][25] this technique has so far not been investigated thoroughly for sarcomas in general or for specific sarcoma entities.…”
mentioning
confidence: 99%